Strengthening Reading Literacy for Students In Islamic Elementary Schools - Pamuji, Zuri (International Proceedings of Nusantara Raya, 2022)
Reading literacy is the ability to understand, use, evaluate, and reflect on various written texts to develop individual capacities to contribute positively to society. Reading literacy is essential to be taught and strengthened, especially for elementary school-aged children. This study aims to describe in-depth supporting reading literacy in first-grade students at MI Muhammadiyah Pasir Lor Banyumas. The research method is descriptive-qualitative, with interviews, documentation, and observation as data collection techniques. The results showed that strengthening reading literacy in the institution was carried out through two main methods: the learning process and other ways. The reinforcement is focused on the level of understanding and using existing literacy. This is done according to the stage of student development, learning materials, and the level of competence at that class level. The reinforcement can have a good impact on students' literacy skills.